Global Nonexistence for a system of nonlinear viscoelastic wave equations with p-Laplacian operator - Quispe Méndez, Teófanes (2019)
We consider a mixed problem for a system of nonlinear viscoelastic wave equations with p-Laplacian operator. Under certain conditions on the relaxation functions and the source terms, using the indirect method, we prove a result of global nonexistence for certain solutions with nonpositive initial energy as well as with positive initial energy.